A simultaneous pancreas-kidney transplantation for type 1 diabetes mellitus after a long-term of receiving hemodialysis renal replacement therapy. Clinical сase - R. Kh. Salimkhanov; M. I. Yevloyeva; A. S. Severina; M. Sh. Shamkhalova; N. P. Trubitsyna; Y. G. Moysyuk (Сахарный диабет)
At the present time, a simultaneous pancreas-kidney transplantation (SPKT) is an effective method of treatment for patients on renal replacement therapy by hemodialysis program in the outcome of the terminal stage of diabetic nephropathy. This method of treatment solves several problems: it reduces the severity of intoxication syndrome, contributes to the achievement of euglycemia in most cases, which certainly allows to slow the progression of micro- and macrovascular complications of diabetes. Despite of positive effect of euglycaemia and kidney function normalization, the accumulated metabolic memory legacy of long-term uncompensated diabetes mellitus is realized, which makes a posttransplantational rehabilitation of patients difficult. A duration of hemodialysis therapy is known as a cardiovascular events risk factor, which affects the surgery result and favorable posttransplant period. More often after successful SPKT microvascular diabetic complications are stabilized, but macrovascular diabetic complications, diabetic neuroosteoarthropathy and mineral and bone disease are progressed. That’s why is necessary to perform regular examination after SPKT by a team of specialists, including nephrologist, endocrinologist, cardiologist, ophthalmologist with correction of ongoing therapy. Therefore both the preparation of  the patient for transplantation with the earliest possible placement on the waiting list and the post-transplant rehabilitation afterwards are extremely important.